Redreaming America : toward a bilingual American culture - Castillo, Debra A. (SUNY series in Latin American and Iberian thought and culture., 2005)
"What would American literature look like in languages other than English, and what would Latin American literature look like if we understood the United States to be a Latin American country and took seriously the work by U.S. Latinos/as in Spanish? Debra A. Castillo explores these questions by highlighting the contributions of Latinos/as writing in Spanish and Spanglish."--Jacket